2018
DOI: 10.1002/pssa.201700837
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin Loaded Liposomes for Anti‐Microbial Photodynamic Therapy of Gram‐Positive Bacteria

Abstract: Due to its highly lipophilic nature, poor solubility in aqueous media, and poor bioavailability, the naturally occurring photosensitizer hypericin has a limited therapeutic value. Liposomal encapsulation is a promising solution to overcome these limitations. Use of liposomes as delivery vehicles for hypericin in antimicrobial photodynamic therapy (aPDT) is quite new. The aim of this work is therefore, to prepare various hypericin loaded liposomal formulations viz. DOPE/CHEMS/DPPC, DSPC/DPPC/DSPE-PEG, and DPPC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…It was also observed that photodynamic treatment using an invasomes formulation was even more effective than 1% chlorohexidine, a conventional disinfectant, which caused a bacterial reduction of only 1.2 log CFU. A very recent study concerning the limited use of hypericin (HYP, Figure 34 ) as a PS due to its highly lipophilic nature, poor solubility in aqueous media, and poor bioavailability showed that its incorporation in liposomes could be a promising alternative [ 167 ]. The results revealed that the liposomal formulations of DOPE/CHEMS/DPPC (1,2-dioleoyl- sn -glycero-3-phosphoethanolamine/cholesteryl hemisuccinate/ l -α-dipalmitoylphosphatidylcholine), DSPC/DPPC/DSPE-PEG (1,2-distearoyl- sn -glycero-3-phosphatidylcholine/ l -α-dipalmitoylphosphatidylcholine/1,2-distearoyl- sn -glycero-3-phosphoethanolamine- N -[methoxy(polyethylene glycol)-2000] and DPPC/DOTAP loaded with HYP were able to attain a 2.3–2.5 log reduction of Staphylococcus saprophyticus subsp.…”
Section: Liposomesmentioning
confidence: 99%
“…It was also observed that photodynamic treatment using an invasomes formulation was even more effective than 1% chlorohexidine, a conventional disinfectant, which caused a bacterial reduction of only 1.2 log CFU. A very recent study concerning the limited use of hypericin (HYP, Figure 34 ) as a PS due to its highly lipophilic nature, poor solubility in aqueous media, and poor bioavailability showed that its incorporation in liposomes could be a promising alternative [ 167 ]. The results revealed that the liposomal formulations of DOPE/CHEMS/DPPC (1,2-dioleoyl- sn -glycero-3-phosphoethanolamine/cholesteryl hemisuccinate/ l -α-dipalmitoylphosphatidylcholine), DSPC/DPPC/DSPE-PEG (1,2-distearoyl- sn -glycero-3-phosphatidylcholine/ l -α-dipalmitoylphosphatidylcholine/1,2-distearoyl- sn -glycero-3-phosphoethanolamine- N -[methoxy(polyethylene glycol)-2000] and DPPC/DOTAP loaded with HYP were able to attain a 2.3–2.5 log reduction of Staphylococcus saprophyticus subsp.…”
Section: Liposomesmentioning
confidence: 99%
“…10,12‐tridodecadiynoic acid (TCDA) /phospholipid vesicles and TCDA/photosensitizer/phospholipid vesicles were assembled into a matrix with good morphology, and the uniform distribution of the liposome diameter was confirmed by SEM, TEM, and DLS. Compared with TCDA/phospholipid vesicles (136.8 nm), TCDA/photosensitizer/phospholipid vesicles had larger diameters (191.7 nm) because of the loading of photosensitizers, which results in a slight increase in lipid vesicles due to the high deformability of the phospholipid double layer …”
Section: Methodsmentioning
confidence: 99%
“…Compared with TCDA/ phospholipid vesicles (136.8 nm), TCDA/photosensitizer/ phospholipid vesicles had larger diameters (191.7 nm) because of the loading of photosensitizers, which results in a slight increase in lipid vesicles due to the high deformability of the phospholipid double layer. [28] Compared with that of phospholipid vesicles, incorporation of TCDA resulted in a significant increase in temperature, possibly because of the packing effect of the TCDA/lipid bilayer. The phospholipid vesicles feature a liquid crystalline phase at room temperature, leading to the release of payloads if no TCDA structure is applied to the bilayer.…”
mentioning
confidence: 99%
“…Liposomal hypericin ( Hyp ) exerts antitumor, antiangiogenic effects [ 76 ] and anti ‐Gram‐positive bacteria activity. [ 77 ] Caeano et al. studied Hyp in DPPC liposomes ( Figure 4 ).…”
Section: Construction Of Liposomal Systems For Pdtmentioning
confidence: 99%